Analisis Penerapan Literasi Dan Numerasi Matematika Di SD Negeri Alur Punti - Sujoko Waluyo (Jurnal Pustaka Cendekia Pendidikan, 2024)
This research aims to determine the application of mathematics learning in the Merdeka curriculum. This research uses a qualitative method with a case study approach, data analysis techniques using triangulation techniques to confirm data based on the results of observations, interviews and documentation. Researchers concluded that the implementation of differentiated learning was successfully implemented by mathematics teachers. Teachers use content differentiation, process differentiation, and product differentiation.  Different learning outcomes have a positive impact on both teachers and students. Through differentiated learning, teachers feel happier because students become more involved and aware. This is reflected in the very creative products produced by students in their learning. However, considering the challenges teachers face at the differentiation process stage, teachers are still confused when differentiating the material they provide to different students